The slave ship a human history - Rediker, Marcus (Penguin Books, 2008)
For more than three centuries, slave ships carried millions of people from the coasts of Africa to the New World. Here, award-winning historian Rediker creates a detailed history of these vessels and the human drama acted out on their rolling decks. Rediker restores the slave ship to its rightful place alongside the plantation as a formative institution of slavery, as a place where a profound and still haunting history of race, class, and modern capitalism was made.--From publisher description.